The False cognates in enology and gastronomy: a study in english and spanish - Osório Cardoso, Maria Ivone (2012)
This paper will focus on some aspects of translation based on blending distinct linguistic domains such as the vocabulary of Hotel Industry, of Enology and Gastronomy in Spanish by tertiary level students (2nd year) of the course of Hotel Management. Portuguese students, most of the times, rely on a L1 (Portuguese) general language, namely using false cognates in the above mentioned areas in the Spanish and English classes in, at a first sight helpful but misleading way, hoping to succeed by using the word that seems correct to the context, when there isn’t, because: •they choose a word suitable to the context in L2, but the choice of that word is often misleading, by relying in a false L1 reality that is going to adulterate reality in the L2 domain, •but it seems that the opposite is also true, and takes place too; The difficulty in making such type of distinctions is due to: •the lack of linguistic and lexical knowledge; • the need to study the cause of these chromaticisms, by: • being in touch with specific literature; . working, not only with their peers, but also with their language teacher to develop strategies to diminish and, if possible, to eradicate this type of linguistic and, mainly translation problem, that causes so many learning constraints.